Subcutaneous canine fossa aspergilloma to intervene or not - case report - Munjal, Manish; Garg, Vikas; Rishi, Porshia; Sidhu, Harjinder; Munjal, Shubam; Talwar, Shivam; Sharma, Salony; Chawla, Deeksha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
The term “Aspergillosis” refers to an illness due to allergy, airway or lung invasion, cutaneous infection, or extrapulmonary dissemination caused by species of Aspergillus. A 51-year-old male with a history of swelling in the right maxillary region is presented. The diagnosis was subcutaneous aspergillosis in an immunocompromised patient, which was successfully treated with voriconazole and surgical excision of the mass. Possible clinical manifestations, diagnostic imaging techniques and treatment used are highlighted upon. Patient was taken up for premaxillary mass excision by sublabial approach. Sublabial incision was given in the upper gingivo-buccal sulcus from right canine upto the first molar, the canine fossa and a subcutaneous mass was dissected from anterior wall of maxilla Histopathological report was consistent with fungal granuloma with predominant hyphae of aspergillus. Patient was prescribed voriconazole 200 mg twice a day with weekly monitoring of liver functions.